PENINGKATAN KEMAMPUAN MENYIMAK MELALUI MEDIA FOLKLOR “PETUALANGAN KE AIR TERJUN DEDARI” PADA SISWA KELAS IV SD BALI BILINGUAL SCHOOL - Wahyu Nurhidayati (STKIP Subang, 2026)
This study aims to improve the listening skills of fourth-grade students at SD Bali Bilingual School in Indonesian language subjects through the application of local folklore media entitled